Glycoprotein IIb/IIIa Receptor Inhibitors in Patients with ST-Segment Elevation Myocardial Infarction and Primary Percutaneous Coronary Intervention - A. S. Tereshchenko; Е. V. Merkulov; A. M. Samko (Столичная издательская компания, 2020)
Recently, there has been a positive trend to reduce mortality from myocardial infarction. One of the reasons for such dynamics is the development of angiographic service in our country and the increase in the number of primary percutaneous coronary interventions. One of the most serious complications of endovascular interventions affecting the prognosis is the development of the phenomenon of slow or unrecoverable blood flow (≪slow/no-reflow≫ phenomenon). The reason for the development of this phenomenon is associated, first of all, with distal embolization by thrombotic masses and fragments of atherosclerotic plaque. In order to prevent this complication, manual thromboextraction was developed - the aspiration of thrombotic masses from the infarct-related artery. The manual thrombus aspiration has not been proven effective in a number of large randomized trials. In addition to the lack of influence on the prognosis, the method of manual thrombus aspiration significantly more often led to the development of ischemic strokes and currently should not be routinely carried out. Another method of preventing the phenomenon of delayed or unrecoverable blood flow is the use of glycoprotein IIb/IIIa receptor inhibitors which is, in contrast to the instrumental method, effective and relatively safe. According to a number of large randomized trials, drug treatment of this complication influences life expectancy in patients with ST-elevation myocardial infarction. At a time when there is already a meta-analysis on the routine use of glycoprotein IIb/IIIa receptor inhibitors during primary percutaneous coronary intervention and their positive impact on survival, in our country, unfortunately, the importance of these drugs is underestimated and according to the register they are used only in 3% of patients with ST-segment elevation myocardial infarction. This review presents studies and comparisons of glycoprotein IIb/IIIa receptor inhibitors existing on the market.